2017
DOI: 10.1038/nn.4649
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-specific astrocyte gating of amygdala-related behavior

Abstract: The amygdala plays key roles in fear and anxiety. Studies of the amygdala have largely focused on neuronal function and connectivity. Astrocytes functionally interact with neurons, but their role in the amygdala remains largely unknown. We show that astrocytes in the medial subdivision of the central amygdala (CeM) determine the synaptic and behavioral outputs of amygdala circuits. To investigate the role of astrocytes in amygdala-related behavior and identify the underlying synaptic mechanisms, we used exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
239
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 257 publications
(260 citation statements)
references
References 63 publications
16
239
1
4
Order By: Relevance
“…Therefore, restoration of CB 1 receptor expression in astrocytes and astroglial mitochondria could represent a new approach to assess the function of the tripartite synapse. CB 1 receptors in astrocytes play a key role in the two‐way communication between neurons and astrocytes through rising calcium in astrocytes that modulates synaptic transmission and plasticity (Araque, Castillo, Manzoni, & Tonini, ; Gómez‐Gonzalo et al, ; Martin‐Fernandez et al, ; Navarrete & Araque, ; Navarrete et al, ; Navarrete, Diez, & Araque, ). Astroglial CB 1 receptor activation regulates astrocytic D‐aspartate uptake (Shivachar, ) and might contribute to the brain´s energy supply through the control of leptin receptors expression in astrocytes (Bosier et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, restoration of CB 1 receptor expression in astrocytes and astroglial mitochondria could represent a new approach to assess the function of the tripartite synapse. CB 1 receptors in astrocytes play a key role in the two‐way communication between neurons and astrocytes through rising calcium in astrocytes that modulates synaptic transmission and plasticity (Araque, Castillo, Manzoni, & Tonini, ; Gómez‐Gonzalo et al, ; Martin‐Fernandez et al, ; Navarrete & Araque, ; Navarrete et al, ; Navarrete, Diez, & Araque, ). Astroglial CB 1 receptor activation regulates astrocytic D‐aspartate uptake (Shivachar, ) and might contribute to the brain´s energy supply through the control of leptin receptors expression in astrocytes (Bosier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…CB 1 receptors in astrocytes, but not in glutamatergic or GABAergic synaptic terminals, are responsible for long‐term depression of synaptic efficacy at hippocampal CA3‐CA1 synapses in vivo and the subsequent spatial working memory impairments induced by cannabinoid administration (Han et al, ). Outside of the hippocampus, endocannabinoids acting on astroglial CB 1 receptors in the central amygdala can regulate fear responses by selectively reducing excitatory transmission through synaptic A1 adenosine receptors and increasing inhibitory transmission by synaptic A2A receptors (Martin‐Fernandez et al, ). Over the last decade, extensive study of mitochondrial CB 1 receptors has begun to establish their function and how their activity can modulate behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers have expressed Cre in astrocytes using astrocyte-specific promoters (Glial fibrillary acid protein (Gfap), Glutamate-aspartate transporter (Glast), among others) 3,4 . These astrocyte transgenic mice lines have given us insight into how astrocytes contribute to a variety of behaviors and neurovascular properties 5,6 . It should be noted however that gene expression in astrocytes is heterogeneous between, and even within brain regions; therefore transgene expression in astrocytes can vary considerably 7 .…”
Section: Genetically Targeting Astrocytesmentioning
confidence: 99%
“…This research demonstrated that neurovascular responses are effectively abolished when chelating Ca 2+ in slice culture. Several other drugs targeting astrocytic signaling have been based on the implication of the endocannabinoidbased 5 and ATP-based pathways in astrocytes 45 . Although these pharmacological approaches have been invaluable in uncovering mechanisms of astrocyte function, they can be limited in their specificity, and ability to be used in vivo.…”
Section: Pharmacological Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation